Matematical modeling of the process of enlarging the austenitic grain during high-temperature heating of alloy structural steel - V. A. Kukareko; B. M. Gatsuro; A. N. Grigorchik; A. N. Chichin (Литьë и металлургия)
The influence of the heating rate of a typical case hardening steel 15KHGN2TA and 25KHGT on the growth of austenitic grain during long-term isothermal exposures at the high-temperature chemical-heat treatment was studied. It is shown that the change in the rate of heating case hardening steels in the temperature interval a®g transformations during chemical-thermal treatment has a significant impact on the process of growth of austenitic grains in them.Regression equations describing the dependence of the average size of austenitic grain on the heating rate, pre-annealing temperature and cementation temperature are obtained, which allow selecting the cementation modes of various steels. A phenomenological model describing the mechanism of formation and growth of austenitic grains in steels under heating at different speeds is developed.It is concluded that the slow heating of steels in the interval of phase a®g transformation contributes to the formation of a complex of small austenite grains separated by high angle boundaries with adsorbed on them by impurity atoms, which ensures higher resistance grain structure to coalescence and reduce the rate of migration of the boundaries during prolonged hightemperature austenization.